Assessment of primary care provider and pharmacist knowledge, comfort, and barriers to appropriate inhaled corticosteroid use in chronic obstructive pulmonary disease. Issue 4 (11th January 2023) - Foster, Brooke; Obidare‐Kolade, Daniel; Nagy, Michael
Abstract: Pharmacotherapeutic management of chronic obstructive pulmonary disease (COPD) primarily involves the use of inhaled bronchodilators and inhaled corticosteroids (ICS). Mounting evidence in recent years suggests ICSs should be reserved for a limited COPD population. This study set out to understand primary care pharmacist and primary care provider comfort, barriers, and knowledge regarding appropriate ICS use in COPD. A cross‐sectional, survey‐based study was conducted. The survey was shared with primary care providers and primary care pharmacists at two healthcare organizations in Southeastern Wisconsin. Descriptive statistics were employed to summarize the survey results. The primary outcome was level of comfort, as reported using a 7‐point Likert scale of participants with five statements related to managing ICSs in patients with COPD. Secondary outcomes were level of agreeance, as reported using a 7‐point Likert scale of participants to the existence of seven different barriers to successfully executing ICS de‐escalation. Escalation in patients with COPD who qualify and percentage of participants who correctly answered a select‐all‐that‐apply knowledge‐check question regarding appropriate patient factors for ICS de‐escalation. Participants were most uncomfortable with creating a tapering schedule for ICS de‐escalation. Most participants agreed that many barriers exist to executing appropriate ICS de‐escalations. Twenty percent of all participants answered the knowledge‐check question completely correctly. The study's findings suggest the surveyed primary care providers and pharmacists are uncomfortable with several aspects of COPD management. There are many barriers that prevent clinicians from de‐escalating ICSs in appropriate patients. Clinicians may have knowledge gaps regarding what factors make patients appropriate for ICS de‐escalation.